The World Development Report 2012 "Gender Equality and Development": conceptual turning point: but no change in practice? - Elke Herrfahrdt-Pähle; Birte Rodenberg (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
For the first time, the World Bank devotes one of its most influential publications in the world of opinion, the World Development Report for 2012, to the issue of Gender Equality. Based on studies of profound quality, the World Development Report (WDR) 2012 begins by documenting progress – e.g. the improved access of girls and women to education – and obstacles – like massive inequality in the areas of socio-political participation - on the road to increased gender equality. In addition, and for the first time, gender equality is recognized as a development goal in its own right. In the form of references to the normative and legal reference framework of the United Nations – i.e. the Millennium Development Goals (MDGs) and the Convention on the Elimination of Discrimination Against Women (CEDAW) – there is also a clear-cut politicization of the gender issue. Noteworthy in this regard are not so much the results of the report, since the trends of this heterogeneous development of global gender relations have been known since the review of the MDGs. Rather, it is striking that the World Bank is calling attention in its World Development Report to central insights gained by the international women's movement – quite contrary to the instrumentalising credo which it has stood behind for many decades, namely that economic growth is good for equal opportunities and that equal rights for women are simultaneously an important precondition for increased productivity and market growth. Thus the Bank is recognizing for the first time the importance of agency and collective negotiating processes for empowerment processes in bringing about change in existing societal hierarchies and patterns of discrimination. But it also analyses the strong binding forces of informal institutions, such as cultural norms and traditions, in the assignment of gender-specific roles. On the other hand, this conceptual innovation goes contrary to business operations whose programs continue to have only an inadequate gender-sensitive orientation in spite of the efforts of some sectors. Thus, although its recommendations remain inadequate and its impact on the practical work of the Bank remains to be seen, the World Development Report is a conceptual step in the right direction. In order to further pursue the path laid out by this World Development Report, the World Bank should begin by contributing even more funding to the MDG 3; it should again introduce country-specific Gender Assessments and should adapt the current Gender Transition Plan for implementation of the World Bank's gender policies to the gender approach propounded in the WDR.
Keywords: 330; Demokratie und Autokratie; Regionale + globale + transnationale Governance; Gender